The Effect of Compulsory Sports Activities on Substantia Nigra Tissue and Behavioral Tests Induction Parkinsons Model with 6-Hydroxydopamine in Prenatal Stress Rats - Toraj Mohammad zamani (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Īlām, 2019)
Introduction: Prenatal stress causes brain alteration and prolongs effects on structure and function. Parkinson's is a progressive neurodegenerative disease And one of the factors motive Parkinson's is the Prenatal stress. Exercising activity is a good way to prevent the disease. The aim of this study was to investigate the effect of mandatory exercise on Substantia nigra tissue in Perinatal Parkinson's rats.